Survival Analysis Based on Clinicopathological Data from a Single Institution: Chemotherapy Intensity Would Be Enhanced in Patients with Positive Hormone Receptors and Positive HER2 in China Who Cannot Afford the Target Therapy. (30th July 2013) - Li, Jianyi; Jia, Shi; Zhang, Wenhai; Zhang, Yang; Fei, Xiang; Tian, Rui
Abstract : Background . Immunohistochemical markers were often used to classify breast cancer into subtypes. The aim of this study was to estimate death and tumor progression for patients with the major subtypes of breast cancer as classified using immunohistochemical assay and to investigate the patterns of benefit from the therapies over the past years. Methods . The study population included primary, operable 199 invasive ductal breast cancer patients, with the median age of 51.1 years old. All patients underwent local and/or systemic treatments. The clinicopathological characteristics and clinical outcomes were retrospectively reviewed. The expression of estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2, and Ki67 was analyzed by immunohistochemistry. All patients were classified into the following categories: luminal A, luminal B, HER2 overexpression, and triple-negative subtypes. Result . The median follow-up time was 33 months. Luminal A tumors had the lowest rate of tumor progression (0%, P = 0.006 ), while luminal B, HER2 over-expression, and triple-negative subtypes were associated with an increased risk of tumor progression (15.4, 19.2, 15.4%). Clinicopathological subtypes retained independent prognostic significance (P = 0.008 ). There were significant differences by Cox model analyzed in age, menopause, lymph node metastasis, and HER2 for the event of death and tumor progression (P < 0.05 ), and there were significant differences only in chemotherapy for the event, respectively (P < 0.05 ). Conclusion . Clinicopathological subtypes of breast cancer could robustly identify the risk of death and tumor progression and were significant in making therapeutic decision. HER2 was the important poor indicator. The chemotherapy intensity would be enhanced for patients with luminal B, especially for HER2 over-expression subgroup.